Aphrodite : goddess of love and beauty - Temple, Teri.; Squier, Robert (Mankato, MN : Child's World, 2013)
An introduction to Greek mythology that shares the stories and myths about the Greek goddess Aphrodite, goddess of love and beauty.
Includes bibliographical references (p. 32) and index.
Booklist
Library Media Connection
Booklist, January 2013
Library Media Connection, May 2013
4.9
Keywords: Aphrodite (Greek deity) -- Juvenile literature; Mythology, Greek -- Juvenile literature; Aphrodite (Greek deity); Mythology, Greek; Aphrodite (Greek deity); Greek mythology